Trusting the trust game: An external validity analysis with a UK representative sample - Sanchayan Banerjee; Matteo M. Galizzi; Rafael Hortala Vallve (Games, 2021)
Using a nationally representative sample of 1052 respondents from the United Kingdom, we systematically tested the associations between the experimental trust game and a range of popular self-reported measures for trust, such as the General Social Survey (GSS) and the Rosenberg scale for self-reported trust. We find that, in our UK representative sample, the experimental trust game significantly and positively predicts generalised self-reported trust in the GSS. This association is robust across a number of alternative empirical specifications, which account for multiple hypotheses corrections and control for other social preferences as measured by the dictator game and the public good game, as well as for a broad range of individual characteristics, such as gender, age, education, and personal income. We discuss how these results generalise to nationally representative samples from six other Organisation for Economic Co-operation and Development (OECD) countries (France, Germany, Italy, Korea, Slovenia, and the US).
Keywords: 330; altruism; cooperation; GSS; reciprocity; Rosenberg; trust; trustworthiness